Development of Local Wisdom-Based Literacy Modules for Reading Comprehension in Elementary School - Gorby Sergeyevich Muhammad Rasyid; Otang Kurniaman; Guslinda Guslinda (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research is motivated by 21st-century learning which is centred on patterns of students' reading literacy comprehension, which is linked to the concept of local wisdom as a strategy for implementing local wisdom-based reading literacy in the form of teaching materials or modules as an effort to build insight, knowledge, personality, mentality and morality for students.  This study aims to develop local wisdom-based literacy modules for teaching reading comprehension in elementary schools that are feasible to use. This research is a Research and Development (RD), using the 4-D Model (Define, Design, Development, and Disseminate). The results of product validation data by media, material and language experts using percentage and category descriptive techniques to show the module's validity, practicality/feasibility. This research was carried out in an elementary school in Pekanbau. The results of the validation by the media expert validator and the material and language expert validator obtained a score of 0.848 in stage II and 0.924 in stage II, so it was categorized as very valid for use. The content and language validation results achieved a score of 0.578 in stage I and 0.800 in stage II, indicating a categorization ranging from valid to highly valid.   The local wisdom-based literacy module testing yielded student learning results with an average score of 84.54, indicating excellent performance.  The results of the student practicality test obtained an overall average of 90.67% and the teacher's practicality test of 88.33%. From the overall average practicality test, students and teachers are categorized as very practical and feasible to use or disseminate. Based on the data above, this research is expected to have implications academically, especially to elementary school as a reference source in developing literacy modules based on local wisdom in literacy learning.